2017
DOI: 10.1016/j.bjm.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome of Nocardia farcinica TRH1, a linear and polycyclic aromatic hydrocarbon-degrading bacterium isolated from the coast of Trindade Island, Brazil

Abstract: Here, we report the draft genome sequence and annotation of Nocardia farcinica TRH1, a petroleum hydrocarbons degrading Actinobacteria isolated from the coastal water of Trindade Island, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Thus, these degradation functions may be involved in disease resistance of P. notoginseng . Moreover, previous studies reported that many microbes can degrade plant exudates and stable pollutants in soil, such as polycyclic aromatic hydrocarbon, benzoate and chlorophenols (Orro et al, 2015; Park & Kim, 2003; Rodrigues et al, 2016; Solvanikova & Golovleva, 2015). The prevalence of these degradation pathways may also suggest that P. notoginseng core rhizosphere microbes degrade notoginseng allelochemicals, such as phenols (Bi et al, 2010) and saponins (Yang et al, 2015), as well as potential exogenous pollutants to reduce the autotoxicity of P. notoginseng .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these degradation functions may be involved in disease resistance of P. notoginseng . Moreover, previous studies reported that many microbes can degrade plant exudates and stable pollutants in soil, such as polycyclic aromatic hydrocarbon, benzoate and chlorophenols (Orro et al, 2015; Park & Kim, 2003; Rodrigues et al, 2016; Solvanikova & Golovleva, 2015). The prevalence of these degradation pathways may also suggest that P. notoginseng core rhizosphere microbes degrade notoginseng allelochemicals, such as phenols (Bi et al, 2010) and saponins (Yang et al, 2015), as well as potential exogenous pollutants to reduce the autotoxicity of P. notoginseng .…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 9 ], a result of the physiological and biochemical pressures imposed by the environmental conditions under which they live [ 10 ]. Their activity in the degradation of polycyclic aromatic hydrocarbon [ 11 , 12 ] focused on them as potential xenobiotic bioremediators.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies revealed that some Nocardia spp. harbor lcp genes, which are responsible for the initiation of the biodegradation of polymeric materials such as rubber ( 4 , 7 10 ). The isolated strain BSTN01 was obtained from the stored water in latex-collecting cups (used to collect the freshly tapped latex from the Hevea brasiliensis trees) thrown away near a local rubber processing unit in Tripura, India.…”
Section: Announcementmentioning
confidence: 99%